2008
DOI: 10.1021/ic8015904
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Oxidation of Ascorbic Acid in Aqueous Solutions by a trans-Dioxoruthenium(VI) Complex

Abstract: The oxidation of ascorbic acid (H(2)A) by a trans-dioxoruthenium(VI) species, trans-[Ru(VI)(tmc)(O)(2)](2+) (tmc = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane), has been studied in aqueous solutions under argon. The reaction occurs in two phases: trans-[Ru(VI)(tmc)(O)(2)](2+) + H(2)A --> trans-[Ru(IV)(tmc)(O)(OH(2))](2+) + A, trans-[Ru(IV)(tmc)(O)(OH(2))](2+) + H(2)A --> trans-[Ru(II)(tmc)(OH(2))(2)](2+) + A. Further reaction involving anation by H(2)A occurs, and the species [Ru(III)(tmc)(A(2-))(Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The reason for the presence of water here is that H 2 A is not soluble in pure CH 3 CN. As the irradiation at λ > 400 nm went on for 1 h, H 2 evolution was clearly observed by GC and dehydrogenated ascorbic acid A, the major product when H 2 A loses its electron and proton, was detected by 1 H NMR analysis (Supporting Information Figure S8). Therefore, it is reasonable to think that the photoinduced electron transfer from the Re(I) complexes to the [FeFe] H 2 ases mimics occurs in the aqueous SDS micelle solution even though the electrochemical window of the SDS micelle is too narrow to detect the redox potential of the complexes directly.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the presence of water here is that H 2 A is not soluble in pure CH 3 CN. As the irradiation at λ > 400 nm went on for 1 h, H 2 evolution was clearly observed by GC and dehydrogenated ascorbic acid A, the major product when H 2 A loses its electron and proton, was detected by 1 H NMR analysis (Supporting Information Figure S8). Therefore, it is reasonable to think that the photoinduced electron transfer from the Re(I) complexes to the [FeFe] H 2 ases mimics occurs in the aqueous SDS micelle solution even though the electrochemical window of the SDS micelle is too narrow to detect the redox potential of the complexes directly.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4, photocatalytic H 2 evo- www.chemsuschem.org lution was achieved in the presence of all these five electron donors, demonstrating the versatility of the [Fe 2 S 2 ]/ZnS hybrid catalyst system. The oxidation potentials of these five electron donors are in the order ascorbic acid < TEOA < TEA < lactic acid < acetic acid (that is, 0.71 V [15] < 0.82 V [16] < 0.93 V [17] < 1.34 V [18] < 1.58 V [19] vs. NHE), which means that basic TEOA and TEA are more easily oxidized than lactic acid and acetic acid. However, the photocatalytic activity of the hybrid system in the presence of basic reagents was lower than with the acidic ones (Figure 4).…”
Section: A Hybrid Photocatalytic System Comprising Zns As Light Harvementioning
confidence: 99%
“…From these NMR experiments, it became apparent that [ 1 ] 6+ can act as a catalyst for oxidation of ascorbic acid. This characteristic is known for Ru-complexes, and it was for instance shown that NAMI-A can be reduced by a variety of agents present in vivo , including ascorbic acid . The ability of [ 1 ] 6+ to oxidize ascorbic acid might have an important biological significance, since ascorbic acid typically reacts with oxidants of the reactive oxygen species (ROS), usually hydroxyl radicals formed from hydrogen peroxide.…”
Section: Reactions With Biological Ligandsmentioning
confidence: 99%